The effectiveness of nonsteroidal anti-inflammatory agents in the treatment of pelvic inflammatory disease: a systematic review - Dhasmana, Divya (BioMed Central, 2014)
BACKGROUND: Pelvic inflammatory disease (PID) is the result of infection ascending through the endocervix to the uterus and fallopian tubes. Inflammation driven by infected host cells appears to be central to the development of tissue damage and associated reproductive complications. Nonsteroidal anti-inflammatory agents (NSAIDs) therefore have the potential to reduce the sequelae associated with pelvic infection. METHODS: A search of four electronic reference databases, an internet search for relevant grey literature and a review of the bibliographies of identified publications was used to identify studies evaluating NSAIDs in the management of PID. A predefined search strategy was used to identify studies that included women with PID aged over 16 and diagnosed after 1980. Randomized controlled trials, nonrandomized controlled trials, and cohort studies with comparison group data were included without language restriction. Two reviewers independently assessed the studies against agreed criteria and extracted relevant data using a standardized pro forma. A meta-analysis to calculate the relative risk associated with NSAID use was planned if appropriate. RESULTS: Forty-three studies were identified. After reviewing abstracts or full texts, two randomized controlled trials were found to meet the selection criteria for inclusion. The use of NSAIDs was reported to improve tubal patency, reduce pelvic adhesions and reduce suprapubic pain but the studies were of poor quality with a high risk of bias. Meta-analysis of the data was not performed. CONCLUSIONS: Insufficient data is available to support or refute the efficacy of NSAIDs in the prevention of short or long-term complications of PID.